PEMAHAMAN KOLABORATIF TEKSTUAL DAN KONTEKSTUAL TERHADAP AL-QUR’AN DALAM MEMBENTUK SIKAP MODERAT BERAGAMA - Abdul Muqit, Ade (Institut PTIQ Jakarta, 2024)
The Qur'an is a holy book that is a guide for mankind (hudan linnas), but in order for humans to find the instructions in the Qur'an, humans must try to understand it. Understanding the Qur'an is not an easy matter because it must fulfill various strict requirements in it so that although the truth of interpretation of the Qur'an remains relative, not everyone can do it. There are two approaches used to understand the Qur'an, namely textual and contextual. Textual and contextual approaches have always colored the journey of Muslims. This research is a library research, which is a research that uses literature in its implementation. The results of this study indicate that the collaboration of textual and contextual understanding has a very important role in shaping a moderate attitude in religion